Cell-free multi-layered collagen-based scaffolds demonstrate layer specific regeneration of functional osteochondral tissue in caprine joints. (May 2016) - Levingstone, Tanya J.; Ramesh, Ashwanth; Brady, Robert T.; Brama, Pieter A.J.; Kearney, Clodagh; Gleeson, John P.; O'Brien, Fergal J.
Abstract: Developing repair strategies for osteochondral tissue presents complex challenges due to its interfacial nature and complex zonal structure, consisting of subchondral bone, intermediate calcified cartilage and the superficial cartilage regions. In this study, the long term ability of a multi-layered biomimetic collagen-based scaffold to repair osteochondral defects is investigated in a large animal model: namely critical sized lateral trochlear ridge (TR) and medial femoral condyle (MC) defects in the caprine stifle joint. The study thus presents the first data in a clinically applicable large animal model. Scaffold fixation and early integration was demonstrated at 2 weeks post implantation. Macroscopic analysis demonstrated improved healing in the multi-layered scaffold group compared to empty defects and a market approved synthetic polymer osteochondral scaffold groups at 6 and 12 months post implantation. Radiological analysis demonstrated superior subchondral bone formation in both defect sites in the multi-layered scaffold group as early as 3 months, with complete regeneration of subchondral bone by 12 months. Histological analysis confirmed the formation of well-structured subchondral trabecular bone and hyaline-like cartilage tissue in the multi-layered scaffold group by 12 months with restoration of the anatomical tidemark. Demonstration of improved healing following treatment with this natural polymer scaffold, through the recruitment of host cells with no requirement for pre-culture, shows the potential of this device for the treatment of patients presenting with osteochondal lesions.